A comparative study for estimation of Losartan Potassium drug by atomic absorption technique and UV-visible spectrophotometry - Walaa Hazim Hameed Aljanabi; Sarhan Ali Salman; Saleh Abdullah Ahmed (Tikrit Journal of Pure Science, 2023)
Atomic absorption technique is used to determine losartan potassium through the quantitative detection of potassium (K) element in the drug. the extraction was carried out by acid digestion and the percentage recovery is 97.2%, the error percentage is -2.8, detection limit is 0.038 μg /ml, and the relative standard deviation did not exceed 2.58%. The results were compared with UV-Visible technique method with percentage recovery of 96.5%, detection limit is 0.93 μg / ml and the relative standard deviation was not more than 1.55%.